What is the implementation practice of schools as learning organisations from the perspective of local governments? - Inese Lusena-Ezera; Gunta Siliņa-Jasjukeviča (Acta Paedagogica Vilnensia)
The approach of the school as a learning organisation was updated in the world with rapid changes in teaching and learning processes, in the governance of educational institutions and learning content and learning outcomes. Introducing, promoting and strengthening the approach of schools as learning organisations can also be observed in the field of education in Latvia. The learning organisation approach is based on cooperation between different parties to achieve common learning goals. In order to introduce, implement and strengthen the changes initiated in education in Latvia, it is necessary not only to develop cooperation between the different stakeholders, including the cooperation between the educational institution and its founder, particularly the municipality, but also to understand whether all stakeholders, especially municipalities, fully understand the approach of the school as a learning organisation when facilitating educational institutions to become learning organisations. The aim of the study was to find out the practice of the school as a learning organisation approach in education institutions in Latvia from the perspective of Latvian local governments. It was find out that the implementation of Latvian education policy in the context of school as a learning organisation in local governments does not take place within a single, unified system. It was identified that the obstacles or difficulties identified by local governments in the implementation of school as a learning organisation are applicable both at the level of education policy planning, at the whole-school level and at the school management level, furthermore, modelling and growing learning leadership is one of the weakest dimensions of the school as a learning organisation in educational institutions.